Antimicrobial susceptibility patterns of Î²-lactamase producing Staphylococcus Aureus (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi:10.3329/jafmc.v4i2.1838JAFMC Bangladesh Vol.4(2) 2008 14-17